Basic nutrition concepts & nutrition indicators:Training manual for project management unit members - Ekesa, Beatrice; Nabuuma, Deborah; Namukose, Samalie; Upenytho, George (2018)
This training guide is intended to build capacity of Project management Team to transfer knowledge on basic concepts regarding appropriate dietary patterns and use of existing farming systems for better household nutrition. In referring to this manual, the Project management team will be able to transfer the information gained to community level field extension workers. The expected impact is that enhanced knowledge of the links between agriculture, nutrition and health, formation and/or upgrading of existing home gardens into comprehensive gardens as well as proper dietary and health practices will eventually lead to enhanced nutrition and health status.